Learning on the Job: Understanding the Cooperative Education Work Experience - Griffith, Alison I. (Education Policy Analysis Archives, 1993)
Cooperative learning programs in Ontario provide on the job learning experiences for students. This paper analyzes three cases of student work placements described in extensive interviews with students, teachers and co-workers. Some students had enjoyed their work experience while others had not. When the student experiences were situated in the socially organized work processes of the work sites, the diverse experiences were found to have a common theme. When students are able to participate in and make sense of the work process, their work placement experience was seen to be useful for making future employment decisions. Where students were marginal to the work process, their lack of knowledge often translates into an unpleasant work experience and decisions about employment based on an experience of failure. This article suggests that our understanding of student learning on the job would be strengthened by a focus on the socially organized work process.